An Optimal Approach to Study the Nonlinear Behaviour of a Rotating Electrical Machine - Nicolae Herişanu; Vasile Marinca (Journal of Applied Mathematics)
We introduce a novel analytical approximate technique, called Optimal Variational Method (OVM), to investigate the nonlinear behaviour of a rotating electrical machine modelled as an oscillator with cubic elastic restoring force and time variable coefficients. The proposed procedure involves the presence of some initially unknown convergence-control parameters whose values are later optimally determined. Comparisons between the obtained results and exact ones reveal that OVM is very effective and convenient providing highly accurate results.